The decorative in urban Vienna: Its preservation. (1st July 2013) - Koller, Manfred
Abstract : The Vienna cityscape has retained its nucleus of the Roman fort through Medieval times to the present. Since the thirteenth century it has been enlarged, and its outlines changed again with the building of new fortifications in the sixteenth and seventeenth centuries. Gardens spread around the perimeter during the eighteenth century until the building of the new Ringstraße after 1857 replaced the dismantled bastions. Vienna's cathedral, the Court, palaces, public and private houses with characteristic built features including details such as pavings, lighting or railings, symbolic ornaments on buildings or in public spaces, all illustrate aspects of the decorative. In 1864-1874 the first museum and school for applied arts in mainland Europe set new standards for techniques and design of decoration. In 1889 Camillo Sitte in his book on urban architecture promulgated the idea of retaining historic details in growing cities, and regarding them as artistic creations. In 1895-1905 plans to adapt the narrow city streets for modern traffic following the example of Paris would have destroyed large areas, but the plans were cancelled in time. Adolf Loos rejected superficial ornamentation in 1908 and placed bare white plaster or coloured marble or precious metal on his façades. Around 1900 Otto Wagner had even more influence on the townscape through his own immense oeuvre and the works of his many disciples. Decorations on Viennese façades were made from a variety of stone, lime plaster, lime stucco and since 1847 Roman cement, bare brickwork and glazed tiles, which will be briefly discussed in their historic context, along with aspects of their conservation. Colouring, mainly in 'stone colours', has been examined and can be compared to paintings of the city from the fifteenth century onwards. There is less direct evidence for painted façades from the fifteenth and sixteenth centuries, and only small traces still survive. From the time of the Ringstraße frescoes and sgraffiti have undergone conservation, in recent decades combined with increasingly scientific examination and precise documentation. Major issues in urban conservation within Vienna include the disruption of its skyline by the construction of speculative tall commercial buildings close to protected areas (which include the World Heritage Sites of Schönbrunn designated in 1996, and the city with the Ringstraße and Belvedere, designated in 2001), reduced context for historic façades due to the preservation of the façade but not the interior construction (façadism), expanding the elevation with additional storeys, and aggressive confrontation from new façades made from steel and glass.